Quantifying global warming potential, land use and financial cost of constructed wetland as a post-treatment technology for removing micropollutants from municipal wastewater - Yu Lei; Jorn de Vos; Huub Rijnaarts; Wei-Shan Chen (Cleaner Environmental Systems, 2025)
The occurrence of micropollutants in the aquatic environment shows potential adverse effects towards ecosystems, such as estrogenic effects on the sexual development of fish and the resistance of microorganisms to antibiotics. Constructed wetlands (CWs) can be used as a post-treatment technology to remove micropollutants from the effluent of conventional wastewater treatment plants. Life Cycle Assessment was performed to assess the environmental and economic impacts of two constructed wetlands (i.e. sand-based CW and bark and biochar-based CW), and compared these impacts with other selected wastewater treatment technologies (i.e. ozone and activated carbon-based technologies). Regarding the removal efficiency of MPs, the bark and biochar-based CW showed a higher removal range than other technologies, though a fluctuation of removals exists due to the effect of seasonality. The CW scenarios require larger land to obtain the desired MP removal efficiencies than other technologies. Despite this, using bark and biochar as support matrices can reduce the land use of the CW system (0.51 m2/m3) compared with sand (0.58 m2/m3). The Global Warming Potential and overall treatment costs of the CW scenarios (i.e. the bark and biochar-based CW with 148 g CO2 equivalent/m3 and 0.14 €/m3; the sand-based CW with 108 g CO2 equivalent/m3 and 0.12 €/m3) rank in the middle among the studied technologies. The findings of this research provide valuable support for the decision-making process in selecting a nature-based technology working as a post-treatment of WWTPs for MP removal.